Proximal type epithelioid sarcoma of the vulva - Torres-Cepeda, Duly (2022)
Epithelioid sarcoma is a rare type of mesenchymal tumor. Proximal-type epithelioidsarcoma of the vulva is an extremely rare malignant tumor of the soft tissues withfrequent recurrences due to its aggressive behaviour. Because its characteristicsare similar to other benign lesions, this leads to diagnostic and therapeutic delays.Histologic features of this tumor include prominent epithelioid cells and theappearance of rhabdoid features with marked nuclear atypia. Due to its low incidence,there are no evidence-based diagnostic algorithms or published recommendationsfor treatment. The prognosis is generally poor. A case of proximal type epithelioidsarcoma of the vulva is presented.